Functional Equivalent as a Translation Procedure Used for Translation of Expressive Lexis - GJurchevska Atanasovska, Katarina (St. Kliment Ohridski University of Bitola, 2017)
This paper deals with effectiveness of the procedure functional equivalent used for translating literary texts rich in expressive lexis, which can be regarded as their stylistic feature. The purpose is to draw conclusions on how much this procedure ensures conveying the necessary stylistic effect from the original in the translation as well as on how the analysis of inappropriate translation equivalents can be applied in practice to enhance the potential of translation procedures when working with expressive lexis and to improve translation quality in general.
Keywords: literary translation, functional equivalent, expressive lexis, stylistic effect, translation quality